(untitled) (The Journal of Medicine, Humanity and Media, 2024)
As "Healthy China" becomes a national strategy, health communication is receiving increasing attention from the public. In the era of intelligent interconnection, thanks to the development and transformation of communication technology and methods, health communication presents different characteristics from before. This article uses statistics from the network communication data of health communication cases in 2023, extracts ten typical cases that have received high public attention and are representative, and analyzes the characteristics of health communication at four levels - content themes, communication strategies, communication methods, and user attention - based on multidimensional data. It also summarizes health communication strategies to promote the dissemination and promotion of health information, improve public health literacy, and help health and medical entities cope with the risks and challenges of digital communication.